Sedimentation Rate Analysis Waters in Tegalsari Beach Fishery Port, Tegal - Idris, Muhamad Kemal; Heriyanto, Benny Kemal; Sodik, Suryo Nur; Setyaningsih, Wahyu Adi (Journal of Applied Geospatial Information, 2023)
Tegalsari Coastal Fishing Port (PPP) is a fishing area located in Tegal City and is a port with fairly dense ship activity. With the conditions owned in the Tegalsari PPP, it makes the Coastal Fishing Port with high economic potential. Conditions that affect activities at Tegalsari PPP are the silting of shipping lanes which cause sedimentation in the port pond or in the shipping channel. Therefore, information about bathymetry and sedimentation rate is needed to facilitate shipping flows at PPP Tegalsari. The purpose of this study is to identify hydrooceanographic conditions in Tegalsari PPP, analyze sedimentation rates in Tegalsari PPP and provide recommendations for the results of sedimentation rate analysis. The data used in this study contained 3 data, namely bathymetric data, tidal data and sedimentation rate data. For data processing using Mike 21 software. The results that have been carried out in this study have varied results on bathymetric conditions and sedimentation rates in Tegalsari PPP. The results of bathymetric modeling. In existing conditions PPP Tegalsari has an average depth of 1.2 – 3.6 m, in alternative 1 it has a depth of 3.0 – 7.2 m and in alternative 2 it has a depth of 2.5 – 7.0 m. The sedimentation rate in PPP Tegalsari within the research period of 15 days, namely in existing conditions ranging from 1.095 mm/year, in alternative 1 ranging from 0.438 mm / year and in alternative 2 ranging from 0.486667 mm/year. In the results of the research conducted that the level of sedimentation conditions in Tegalsari PPP is low. Thus, at the time of sedimentation does not affect the shipping channel at PPP Tegalsari.